Thermosphere–Ionosphere Responses Over Thailand During the 2015 St. Patrick's Day Storm: Comparison of Observed O/N 2 and VTEC With the SD WACCM‐X Model Outputs - Paparin Jamlongkul; S. Wannawichian; L. J. Paxton; Clayton Cantrall; Hanli Liu; G. Lu; Pornchai Supnithi; Jirapoom Budtho (Journal of Geophysical Research Space Physics, 2025)
Abstract We present the first comparative analysis of observational data and model results focusing on thermospheric‐ionospheric responses over the Thailand region by studying the St. Patrick's Day geomagnetic storm on 17–18 March, 2015. This study aims to advance our understanding of regional responses by building on previous observation‐model comparisons. The observational data include global O/N 2 ratios from GUVI onboard the TIMED spacecraft, global vertical total electron content (VTEC) from the worldwide GNSS receivers obtained from the Madrigal database, and regional VTEC over Thailand from the KMI6 GNSS station. The atmospheric simulations used are from SD WACCM‐X, incorporating high‐latitude drivers from the Weimer and Assimilative Mapping of Ionospheric Electrodynamics (AMIE) models. The O/N 2 comparison focuses on TIMED's overpasses across Thailand at 3 UT (10 LT) on both days. Both models tend to reproduce general trends in the O/N 2 ratio and VTEC variations prior to the storm onset. The SD WACCM‐X/Weimer model shows better agreement with the O/N 2 ratio from GUVI observations over Thailand, particularly during the recovery phase. Meanwhile, the SD WACCM‐X/AMIE model better captures VTEC trends on both large and localized scales, especially after sunset, and successfully reproduces localized features over Thailand. However, during the early recovery phase, both Weimer and AMIE drivers fail to fully capture the collapse of the equatorial ionospheric anomaly (EIA) as indicated by VTEC data, likely due to overestimated drift values at low latitudes.
Keywords: Ionosphere and magnetosphere dynamics; Earthquake Detection and Analysis; Geomagnetism and Paleomagnetism Studies